Odpowiedzi

2010-01-20T16:38:30+01:00
A) 6b-1+2b=7b+5
b=6
B) 0,4y+1,3-0,6=1,3-0,8y
1,2y=0,6
y=1/2
1 1 1
Najlepsza Odpowiedź!
2010-01-20T16:40:23+01:00
A)
6b - (1-2b) = 7b+5
6b-1+2b=7b+5
6b+2b-7b=5+1
8b-7b=6
b=6

b)
0.4 ( y+13) - 0.6 = 1.3 - 0.8y
0,4y+5,2-0,6=1,3-0,8y
0,4y+0,8y=1,3-5,2+0,6
1,2y=-3,3 |:1,2
y=-2,75

mam nadzieje, że pomogłam :)
2010-01-20T16:41:26+01:00
A) 6b - (1-2b) = 7b+5
6b-1+2b=7b+5
8b-1=7b+5 | -7b
b-1=5 |+1
b=6

b) 0.4 ( y+13) - 0.6 = 1.3 - 0.8y
0,4y+5.2-0,6=1,3-0,8y
0,4y+4,6=1,3-0,8y| +0,8y
1,2y+4,6=1,3 |-4,6
1,2y=-3,3 | :1,2
y=- 2,75

:)